Self-drilling screws for the prevention of dental and skeletal injuries during open reduction and internal fixation of pediatric mandibular fractures - Elavenil Panneerselvam; Anantanarayanan Parameswaran (Wolters Kluwer Medknow Publications, 2022)
Facial trauma in pediatric population predisposes the child to injury of both the developing skeleton and dentition. This article aims to highlight the experience of the authors through a case report, in using self-drilling screws for fixation of mandibular fractures in pediatric age group. The use of self-drilling screws minimizes the complications such as thermal and/or mechanical damage to the developing dentition and the bone. They also provide significant advantages including ease of availability and technique, superior anchorage with primary stability, and minimizing or avoiding permanent damage to the developing tooth germs in the site of fracture. The use of self-drilling screws for mandibular open reduction and internal fixation in children is an easy, reliable, and safe technique which may have significant value addition in preventing inadvertent injury to the developing tooth germs.